Regulation of the acetylcholine/α7nAChR anti-inflammatory pathway in COVID-19 patients - Alice Courties (Nature Portfolio, 2021)
Abstract The cholinergic system has been proposed as a potential regulator of COVID-19-induced hypercytokinemia. We investigated whole-blood expression of cholinergic system members and correlated it with COVID-19 severity. Patients with confirmed SARS-CoV-2 infection and healthy aged-matched controls were included in this non-interventional study. A whole blood sample was drawn between 9–11 days after symptoms onset, and peripheral leukocyte phenotyping, cytokines measurement, RNA expression and plasma viral load were determined. Additionally, whole-blood expression of native alpha-7 nicotinic subunit and its negative dominant duplicate (CHRFAM7A), choline acetyltransferase and acetylcholine esterase (AchE) were determined. Thirty-seven patients with COVID-19 (10 moderate, 11 severe and 16 with critical disease) and 14 controls were included. Expression of CHRFAM7A was significantly lower in critical COVID-19 patients compared to controls. COVID-19 patients not expressing CHRFAM7A had higher levels of CRP, more extended pulmonary lesions and displayed more pronounced lymphopenia. COVID-19 patients without CHRFAM7A expression also showed increased TNF pathway expression in whole blood. AchE was also expressed in 30 COVID-19 patients and in all controls. COVID-19-induced hypercytokinemia is associated with decreased expression of the pro-inflammatory dominant negative duplicate CHRFAM7A. Expression of this duplicate might be considered before targeting the cholinergic system in COVID-19 with nicotine.